Integrated digital marketing communications - Barker, Beverly (Henry Stewart Talks, 2010)
Key digital channels, Search engine marketing, E-mail marketing, Affiliate and partner marketing, Online sponsorship, Interactive advertising, Which formats are best?, Viral marketing, Online PR, Media neutral planning, Every product/ service model will vary, The planning process, Customer segmentation, Business audiences, Media selection
Archived at 2022/04/12